Sleep Spindles Predict Stress-Related Increases in Sleep Disturbances - Dang-Vu, Thien Thanh; Salimi, Ali; Boucetta, Soufiane; Wenzel, Kerstin; O’Byrne, Jordan; Brandewinder, Marie; Berthomier, Christian; Gouin, Jean-Philippe (Frontiers in Human Neuroscience, 2015)
Background and Aim: Predisposing factors place certain individuals at higher risk for insomnia, especially in the presence of precipitating conditions such as stressful life events. Sleep spindles have been shown to play an important role in the preservation of sleep continuity. Lower spindle density might thus constitute an objective predisposing factor for sleep reactivity to stress. The aim of this study was therefore to evaluate the relationship between baseline sleep spindle density and the prospective change in insomnia symptoms in response to a standardized academic stressor. Methods: 12 healthy students had a polysomnography (PSG) recording during a period of lower stress at the beginning of the academic semester, along with an assessment of insomnia complaints using the Insomnia Severity Index (ISI). They completed a second ISI assessment at the end of the semester, a period coinciding with the week prior to final examinations and thus higher stress. Spindle density, amplitude, duration and frequency, as well as sigma power were computed from C4-O2 electroencephalography (EEG) derivation during stages N2-N3 of non-rapid-eye-movement (NREM) sleep, across the whole night and for each NREM sleep period. To test for the relationship between spindle density and changes in insomnia symptoms in response to academic stress, spindle measurements at baseline were correlated with changes in ISI across the academic semester. Results: Spindle density (as well as spindle amplitude and sigma power), particularly during the first NREM sleep period, negatively correlated with changes in ISI (p < 0.05). Conclusion: Lower spindle activity, especially at the beginning of the night, prospectively predicted larger increases in insomnia symptoms in response to stress. This result indicates that individual differences in sleep spindle activity contribute to the differential vulnerability to sleep disturbances in the face of precipitating factors.